Comparison of diagnostic precision for bone metastasis of primary breast cancer between BONENAVI version 1 and BONENAVI version 2. Issue 11 (November 2019) - Okada, Yukinori; Matsushita, Shoichiro; Nakajima, Yasuo; Yamaguchi, Keiichiro; Okuda, Itsuko; Kojima, Yasuyuki; Tsugawa, Koichiro
Abstract : Objective: The aim of this study was to compare the diagnostic precision of bone scintigraphy with BONENAVI version 1 and BONENAVI version 2 in bone metastasis of primary breast cancer. Methods: The subjects were 56 consecutive patients (all women, mean age 59 ± 12.7 years) who underwent bone scintigraphy with 99m Tc-MDP and were diagnosed with bone metastasis of primary breast cancer from January 2012 to November 2014. Bone scintigraphy was performed with BONENAVI version 1 and BONENAVI version 2 to calculate artificial neural network (ANN), bone scan index (BSI), and hot-spot values, with ANN ≥ 0.5 considered to reflect bone metastasis for the calculation of sensitivity. Mean ANN, BSI, hot-spot values, and sensitivity were compared between BONENAVI version 1 and BONENAVI version 2, with P < 0.05 considered a significant difference. Results: With BONENAVI version 1, mean ANN was 0.73 ± 0.29, BSI was 1.47 ± 1.85, the hot-spot value was 12.4 ± 12.5, and sensitivity was 76.8% (43/56). With BONENAVI version 2, the mean ANN was 0.86 ± 0.19, BSI was 1.53 ± 2.09, hot-spot value was 12.9 ± 15.6, and sensitivity was 94.6% (53/56). BONENAVI version 2 yielded significantly better ANN and sensitivity than BONENAVI version 1 (both P < 0.01). Conclusion: BONENAVI version 2 has improved sensitivity for detecting bone metastasis of primary breast cancer compared to BONENAVI version 1.